DESIGN OF SIO2@NI@ZRO2 SANDWICH CORE-SHELL COKE-RESISTANT NANOCATALYST FOR DRY REFORMING OF METHANE - Aghniasari, Hurin
Dry Reforming of Methane (DRM) is a technology for reforming methane by utilizing CO2 to produce synthetic gas in the form of CO and H2, which are precursors for the production process of various chemicals and liquid fuels. Coke-resistant catalyst are needed to prevent catalyst deactivation in DRM reaction due to CO2. This study aims to produce SiO2@Ni@ZrO2 sandwich core-shell for DRM reaction which have good thermal stability and high catalytic activity to prevent catalyst deactivation caused by coke deposition. In this research, the catalyst was designed in the form of sandwich core-shell nanocatalyst with SiO2@Ni@ZrO2 as precursors. The feed gas consist of CH4 and CO2 with a ratio of 3:7. Catalyst characterization includes XRD, BET, TEM, SEM, and EDX. The result of the catalyst performance test conducted at temperature 700 oC, atmospheric pressure, and WHSV 60.000 mL.g-1. h-1 for 480 minutes showed that the SiO2@Ni@ZrO2 catalyst resulted conversion of CH4 and CO2 at 75% dan 46%, yields of H2 dan CO at 31% dan 35%, and H2/CO ratio around 0,42. The result of TGA analysis showed that adding ZrO2 as precursor improve the catalyst’s life by inhibiting catalyst deactivation.